New azhdarchoid pterosaur (Pterosauria, Pterodactyloidea) with an unusual lower jaw from the Portezuelo Formation (Upper Cretaceous), Neuquén Group, Patagonia, Argentina - KELLNER,ALEXANDER W.A. (2017)
ABSTRACT A new azhdarchoid pterosaur from the Upper Cretaceous of Patagonia is described. The material consists of an incomplete edentulous lower jaw that was collected from the upper portion of the Portezuelo Formation (Turonian-Early Coniacian) at the Futalognko site, northwest of Neuquén city, Argentina. The overall morphology of Argentinadraco barrealensis gen. et sp. nov. indicates that it belongs to the Azhdarchoidea and probable represents an azhdarchid species. The occlusal surface of the anterior portion is laterally compressed and shows blunt lateral margins with a medial sulcus that are followed by two well-developed mandibular ridges, which in turn are bordered laterally by a sulcus. The posterior end of the symphysis is deeper than in any other azhdarchoid. This unique construction of the lower jaw suggests the existence of an elaborate interlocking mechanism with the upper jaw. Furthermore, although speculative, it is advocated here that Argentinadraco barrealensis might have used the lower jaw to obtain its prey by cutting or ploughing through unconsolidated sediment in shallow waters, a feeding behavior not previously proposed for pterosaurs.